PENGARUH PERSPEKTIF MODERNIS TERHADAP PERILAKU NASIONALISME PADA SISWA SMA NEGERI 1 BANTAN - Rohmah, Zainur Rohmah; ', Hambali; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study background of the lack of a sense of nationalist, students forget the identity of his own nation, more individualistic and hedonism. This is because students are not able to filter out the influence of modernization that has penetrated into every aspect of life. So writer take the title "Influence of Modernist Perspective on Nationalism on Student Behaviour SMA Negeri 1 Bantan". Formulation of the problem in this research is a modernist perspective How does the behavior of nationalism in the students of SMAN 1 Bantan. This study aims to determine the effect on the behavior of nationalism modernist perspective on students SMA Negeri 1 Bantan. The sample consists of all students of class X, students of class XI and XII CLASS IPS SMAN 1 Bantan. Students who numbered 358 students and was taken by 20% to 72 students. Data collection instruments, namely a questionnaire consisting of 42 questions, 23 questions for the variables X and Y. 19 questions for variable data were analyzed using linear regression. Based on data analysis, there is significant influence on the behavior of nationalism modernist perspective on students SMA Negeri 1 Bantan, this is evidenced by a series of simple regression test between the variables X and Y, obtained F count 7.51 and 3.98 F table value obtained from the study of the distribution list F table with N = 72, at significance level of 5%, thus F count > F table, or 7.51> 3.98. Thus the hypothesis in this study is accepted that there is the influence of the modernist perspective on the behavior of nationalism in the students of SMAN 1 Bantan. Keywords: Modernist Perspective, Behavior Nationalism